The Influence of Sports Activities on College Students’ Social Adaptability - Hu, Lei; Prompanyo, Manoch (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The cultivation of talents has always been the basis of the development of economy, science and technology and the overall strength of all countries. With the further deepening of China’s reform and opening up, the rapid development of the market economy and the gradual improvement of the level of information technology, the education sector is paying more attention to the cultivation of talents in all walks of life in China. As for college students is about to walk into society, how to learned during college all kinds of professional knowledge and skills in the future life and work, how reasonable in the future workplace, properly handle interpersonal relationships, how to better integrate into social life, reflect their own value, and to raise their competitive strength, and observe the rules and regulations, laws and regulations, Have a good moral integrity, set up the correct world outlook, outlook on life, values. All these are closely related to the social adaptability of college students. Physical education is an important way to implement quality-oriented education and cultivate talents with all-round development, which was clearly pointed out in the Guidelines for Physical Education Course Teaching in National Colleges and Universities issued in 2002.In the given physical education teaching objectives also explains that the students are required to show good sports ethics and cooperative spirit as well as correctly deal with the relationship between competition and cooperation.